Household food inflation in Canada - Olena Kostyshyna; Maude Ouellet (Bank of Canada, 2024)
We use Canadian home scanner data to study household food inflation rates during periods of low and high inflation. We find that during the post-pandemic surge in inflation, the actual inflation rates experienced by different households varied more widely. Low-income households faced higher inflation than high-income households. We find that during the highinflation period, households used several strategies to lower the impact of inflation, including shopping more frequently, shopping at more stores or buying more on sale. Canadian households also substituted more toward low-priced products when inflation increased.
Keywords: E21; E30; E31; L81; 330; Inflation and prices